Tests of human auditory temporal resolution: preliminary investigation of ZEST parameters for amplitude modulation detection - Mori, Shuji; Morimoto, Takashi; Murata, Yuto; Okamoto, Yasuhide; Kanzaki, Sho (Frontiers in Neuroscience, 2023)
Auditory temporal resolution plays a critical role in the everyday experience of listening to complex acoustic patterns. Amplitude modulation detection thresholds are widely used to measure auditory temporal resolution. In an attempt to develop a standardized clinical test of auditory temporal resolution, we used ZEST (Zippy Estimation by Sequential Testing, a Bayesian threshold estimation procedure, to measure amplitude modulation detection thresholds. ZEST utilizes prior knowledge about a listener’s thresholds, as represented by a probability density function of the thresholds, and psychometric functions of the listener’s responses. This paper reports a preliminary study in which ZEST parameters that could be used for measurements of amplitude modulation detection thresholds were sought. For this purpose, we created histograms of the detection thresholds for a wide range of modulation frequencies, measured the psychometric functions of amplitude modulation detection, and performed computer simulations of ZEST threshold estimation. The results suggested that, with appropriately-set parameters, ZEST allows for the accurate estimation of amplitude modulation detection thresholds within 20 trials.